How Does the Immune System Enter the Brain? - Mapunda, Josephine A.; Tibar, Houyam; Regragui, Wafa; Engelhardt, Britta (Frontiers in Immunology, 2022)
Multiple Sclerosis (MS) is considered the most frequent inflammatory demyelinating disease of the central nervous system (CNS). It occurs with a variable prevalence across the world. A rich armamentarium of disease modifying therapies selectively targeting specific actions of the immune system is available for the treatment of MS. Understanding how immune cells access the CNS in MS and how immunomodulatory treatments affect neuroinflammation requires a proper knowledge of the special anatomy of the CNS. The brain barriers divide the CNS into different compartments that differ with respect to their accessibility to cells of the innate and adaptive immune system. In steady state, the blood-brain barrier (BBB) limits immune cell trafficking to activated T cells, which can reach the cerebrospinal fluid (CSF) filled compartments to ensure CNS immune surveillance. In MS immune cells breach a second barrier, the glia limitans to reach the CNS parenchyma. Here we will summarize the role of the endothelial, epithelial and glial brain barriers in regulating immune cell entry into the CNS and which immunomodulatory treatments for MS target the brain barriers. Finally, we will explore current knowledge on genetic and environmental factors that may influence immune cell entry into the CNS during neuroinflammation in Africa.